FEM ANALYSIS OF WOODEN JOINTS AND WOODEN STRUCTURE OF THE ELECTRIC CAR’S FRAME : Received: 30th September 2021; Revised: 10th February 2022, 17th February 2022; Accepted: 19th February 2022 - Żur, Alicja; Żur, Paweł; Baier, Andrzej (MATTER: International Journal of Science and Technology, 2022)
The paper covers the topic of FEM analysis (Finite Element Method) of selected types of wood joints and the analysis of the wooden structure, the electric car in the electric car of the frame of the Silesian Greenpower team. The main assumption of the work was to analyze the displacements and stresses in the structure of the frame that result from the actual load on the structure. Selected wooden joints were analyzed in FEM analysis. The paper also presents various techniques for modelling connections between elements, such as connection by nail or screw, cohesive contact, or the MPC beam element considering three different materials: oak, pine, and plywood. The aim of the study and the final stage was the FEM analysis of the wooden structure, the car frame. The actual support points for the frame and the actual loads on the structure resulting from the mass of components such as the driver, batteries, and motor were taken into account. The distribution and values of stresses in the structure were analysed, as well as the total displacements resulting from the loading of the mass elements, as well as the centrifugal force acting on the car during driving in a corner.